Analysis of Digital Marketing Strategy in Increasing ZIS Fundraising at Laznas Yatim Mandiri Sidoarjo - Nurma Fila Anggun Dwi Saputri; Nur Mahani; Safinatus Sovia; Vika Sayyidatul Mukarromah (Journal Of Management Analytical and Solution (JoMAS), 2024)
This study aims to determine the digital marketing strategy carried out in the process of raising Infaq Zakat funds, and Shodaqoh. This study used descriptive qualitative research method. The data used in this study is primary data, which is in the form of interviews with subjects, namely leaders and employees based on criteria set by the researcher. In addition, researchers also used secondary data by the Yatim Mandiri Sidoarjo collection report, where the collection report can describe how ZIS fundraising uses digital channels. The results showed that Yatim Mandiri Sidoarjo used two fundraising methods, namely direct fundraising and indirect fundraising. Good relationships with donors and beneficiaries created in each program are one of the advantages of being able to provide trust to the institution. Collecting through digital marketing at Yatim Mandiri Sidoarjo using social media Instagram, Facebook, and TikTok. In addition, Yatim Mandiri Sidoarjo uses digital payment applications such as mobile banking, Quick Response (QRIS), and e-wallets. Gathering through social media digital marketing at Yatim Mandiri Sidoarjo is said to be less than optimal due to limited human resources. However, in overcoming this, Yatim Mandiri Sidoarjo continues to develop social media, namely by continuing to create interesting and reliable content so that it can attract wider donors. Keyword: Strategy, Digital Marketing, Laznas Yatim Mandiri Sidoarjo, ZIS, Fundraising